Fenofibrate Regulates Visceral Obesity and Nonalcoholic Steatohepatitis in Obese Female Ovariectomized C57BL/6J Mice - Shin, Yujin (Int J Mol Sci, 2021)
Fibrates, including fenofibrate, are a class of hypolipidemic drugs that activate peroxisome proliferator-activated receptor α (PPARα), which in-turn regulates the expression of lipid and lipoprotein metabolism genes. We investigated whether fenofibrate can reduce visceral obesity and nonalcoholic fatty liver disease via adipose tissue PPARα activation in female ovariectomized (OVX) C57BL/6J mice fed a high-fat diet (HFD), a mouse model of obese postmenopausal women. Fenofibrate reduced body weight gain (−38%, p < 0.05), visceral adipose tissue mass (−46%, p < 0.05), and visceral adipocyte size (−20%, p < 0.05) in HFD-fed obese OVX mice. In addition, plasma levels of alanine aminotransferase and aspartate aminotransferase, as well as free fatty acids, triglycerides, and total cholesterol, were decreased. Fenofibrate also inhibited hepatic lipid accumulation (−69%, p < 0.05) and infiltration of macrophages (−72%, p < 0.05), while concomitantly upregulating the expression of fatty acid β-oxidation genes targeted by PPARα and decreasing macrophage infiltration and mRNA expression of inflammatory factors in visceral adipose tissue. These results suggest that fenofibrate inhibits visceral obesity, as well as hepatic steatosis and inflammation, in part through visceral adipose tissue PPARα activation in obese female OVX mice.